Methods of Determination of the Sign of the Thermo-Diffusion Coefficient in Dispersed Liquids - Musil, Ctibor; Stelina, Julius (Communications - Scientific letters of the University of Zilina, 2006)
In this paper three methods of determination of the sign of the thermo-diffusion coefficient (Soret constant) are presented. The first method uses the relation for Soret constant which was derived from the thermo-diffusion equation. This relation permits determination of the sign of the Soret constant as well as its approximate value. The second method is based on the time dependence of the decay of the created diffraction grating. The last method is based on the measurement of the transmission of light by the dispersion liquid.